RELATIONSHIP BETWEEN ANXIETY AND POST-IMMUNIZATION EVENTS (KIPI) OF THE COVID 19 VACCINE - Umi Islamiyah; Nafolion Nur Rahmat; Ro’isah (Media Inovasi Pendidikan dan Publikasi, 2023)
The COVID-19 pandemic can affect the psychology of the wider community, including anxiety. Vaccines are one strategy being used to combat COVID 19. The national immunization program is declared safe and effective, but there is no one type of vaccine that is guaranteed to be free of side effects or AEFI (Adverse Events Following Immunization). This study aims to determine the relationship between anxiety and Adverse Events Following Immunization (AEFI) of the covid 19 vaccine. Correlational analysis and a cross-sectional research design are used in this kind of study. It was conducted in the West Hamlet of Muneng Kidul Village, Sumberasih District, Probolinggo Regency on 30 May-02 June 2022 door to door. The population consists of up to 46 responders who have received a COVID-19 vaccination. Simple Random Sampling is the method of sampling that is employed. There are 41 responders in the samples. The instrument uses the HARS questionnaire sheet and Adverse Events Following Immunization (AEFI). Spearman rank test data analysis. The results showed that most of the anxiety was moderate, namely 21 respondents (51.2%) and the majority of Adverse Events Following Immunization (AEFI) experienced Adverse Events Following Immunization (AEFI), namely 31 respondents (75.6%). According to the results of the spearman rank statistical test, the covid 19 vaccine's AEFI and anxiety levels are related (p-value=0.004 to =0.05). It is desired that individuals who have received the covid-19 immunization will learn more about the covid-19 virus and the covid-19 vaccination independent research in order to lessen anxiety and the occurrence of Adverse Events Following Immunization (AEFI).